In search of new models of scientific communication in electronic environment: case of scientists in the field of social sciences in Croatia - Vrana, Radovan (Array, 2004)
There are many open questions regarding behavior and activities of the Croatian scientists now working in an environment strongly influenced by ever growing number of printed and electronic information resources used for teaching at universities and scientific research. At the present moment, scientists around the world are already going through changes which are transforming the existing communication paradigm in science based on publishing scientific content in printed publications. To discover the status of current developments in area of scientific communication in Croatia (in the field of social sciences), a research study was initiated having in mind issues such as information availability supporting the advancement of scientific communication, changing attitudes of the Croatian scientists in the field of social sciences using networked information resources and, finally, change of context in scientists' working environment which is influencing their decision to publish in electronic publications. Rationale Science is a basic social activity that helps the development of society. It is also a dynamical system, which components are in constant interaction in order to enable transfer of scientific information to all of its components and outside world. Therefore, scientists need adaptable and flexible tools which will enable dissemination of quality scientific material to them, their colleagues and general public. It is a fact that scientific community in Croatia has accepted information technology as a crucial tool for the dissemination of information generated as a result of scientific activities. Today, all scientific institutions in Croatia are connected to the Internet and large number of scientists uses it on daily basis either for research or teaching at the Croatian universities. Despite the availability of information technology to scientists, it is still unknown how scientists from different fields of science really perceive and use the Internet and electronic information resources to advance their research and teaching. Furthermore, development of new electronic information resources could be used in research and teaching requires exploration into scientists' expectations towards the future development of scientific communication and other parties involved in the process of communication in science. Basis for many expectations can be found in availability of high speed networks, widely accepted full text databases offering scientific journals and books, and PCs at scientist's workplace, which have enabled scientists to work in a quality information environment. To achieve and maintain quality, libraries and other institutions offering access to electronic information resources should do more research studies among users about their information needs, preferences and behavior while working in electronic information environment. Results of such research should give us a direct insight into communication habits of scientists suggesting parameters necessary for a creation of advanced information resources (such as digital libraries). These and other reasons were of great importance for initiation of a research among scientists in the field of social sciences in Croatia. The research among the Croatian scientists in the field of social sciences In 2003, a research among the Croatian scientists was carried out in a form of a survey. The aim of the survey was to collect data about the state of use of information technology for the purpose of scientific communication among scientists in the field of social sciences. More specifically, the survey contained 35 questions, divided into three parts: Scientific communication and new technologies, Information resources for research and teaching and Publishing of scientists' papers. The research was carried out at 5 Croatian universities (in Zagreb, Rijeka, Split, Zadar, Osijek) and 16 faculties only in the field of social sciences in Croatia and it included research and teaching staff. The results of the respondents showed frequent and direct communication between scientists for exchange of ideas, research data, opinions, draft papers etc. supported by information technology available to them at universities. The findings also showed that the structure of the active paradigm of scientific communication in the field of social sciences does not differ significantly from the communication paradigm other scientists from the same field of science use in the rest of the world. They also confirmed the interest of the Croatian scientists for the use of electronic information resources which have become integral part of the daily working routine among scientists in the field of social sciences in Croatia. Generally speaking, the results of the survey indicate that the current state of the development of scientific communication can be described as creating pre-conditions for larger dissemination of information in electronic form by understanding user needs and preferences necessary for development of more complex and sophisticated electronic resources such as digital libraries in Croatia. The results also indicate need for more research in certain areas included in this research which require additional attention. This presentation will present excerpts from the research and comment the ways in which scientists in the field of social sciences in Croatia interact and work in electronic environment. As a conclusion, we can say that major changes in creation, processing, storage and dissemination of scientific information initiated by introduction of information technology into scientific community especially during the 1990s when first digital libraries appeared, resulted in scientific communication paradigm shift in many areas of science in many countries. Croatian scientists are no exception to this trend.